Jual Beli secara Online (E-Commerce) dalam Islam - Pauzi Muhammad (NALAR FIQH: Jurnal Hukum Islam, 2014)
Buying and selling is muamalah contract, the contract is carried oaut by the two parties oin which the first party and second party deliver the goods handed over in return, either in the form of money or goods. Where buying and selling online can streamline and streamline time so that one can make buying dan selling with very person anywhere and anytime. All buying and selling over the internet is done without any face-to-face between the parties that accorred was done electronically, based on the foundation of the rule fiqhiyah the buying and selling via online (internet) it is allowed, and valid, unless it is casuitry irregularities, manipulations, froud and the like, it is also legal csuitry applied, which is forbidden. In the problem of buying and selling online, fiqh considers that baying and selling in cyberspace allowed because mashlahah. Mashlahah is a benefit and harm refuse in order to maintain teh goal of personality. When e-commerce was seen as the with draw of trade in Islam, it may be analogous to that first seller is a marchant (internet service provider or ISP), where as buying fondly called customer. Second, the object is to offer goods and services (such as the ordering as-salam) with a variety of information, profile, price list, seen pictures of goods, as well as the official company. Third, sighat (consent-qabul) performed with the payment gateway system/ software support (authorities and monitors) for the acquirer.